Diversion Of Recidivist Children According To Utilitarianism Aspects - Arifah Uswatun Kossah; Sidik Sunaryo (Universitas Muhammadiyah Malang, 2022)
In an act against legal norms, especially criminal law, children must be treated differently from adults. This is because children are a group of naturally weak people children who commit crimes should be lighter than those adults through what is known as restorative justice and Diversion (Indonesian law says it “Diversi”). However, then, Article 7 paragraph (2) of the Juvenile Criminal Justice System Law (Indonesian: UU SPPA), basically states that Diversi is only carried out if the criminal penalty for the act is less than 7 (seven) years and is not a repetition of a crime. Utilitarianism or Utilism puts benefit as the main goal of Benefit here is defined as happiness. So, good or bad or fair or not a law depends on whether the law gives happiness to humans or not. Through a normative juridical study that emphasizes the review of laws and literature studies, the authors find that a utilitarian review of Diversi to recidivist children is very likely to produce broad benefits for many people and has the potential to close the possibility of recidivist children committing criminal acts again. This is because, in Diversi, the benefits of overcoming the consequences of children's actions can be felt by the perpetrator's child, the victim, and their respective families through mutual agreement. In line with that, the principles of implementing the SPPA Law confirm that children must be addressed especially for the protection of their growth and development and to eliminate discrimination that differentiates the process between one child and another. It is hoped that with this literature review, legal products regarding juvenile justice can participate in guaranteeing the rights of recidivism children in Diversi as a method of overcoming crime by children.